Analisis Perilaku Konsumen Terhadap Keputusan Pembelian Iphone Di Kalangan Mahasiswa - Namira Rahmi Rizqia; Nurhasanah; Syamsul Hidayat (Universitas Sains dan Teknologi Komputer, 2024)
Communication is a social process in human life, one thing that is very basic and very necessary in human life. As time goes by, communication technology has become a basic need for various groups, initially telephones were only used to make calls and send messages, now they have developed into smart phones or smartphones which have many features so that smartphones have become an important need and a special priority among today's students. In this research study, many researchers have carried out consumer behavior, purchasing interest and purchasing decisions. Some related results from previous research are as follows: the first research was conducted by SH Amalia and SH Syahril (2017) with the title